Kilometrul 6 : 1st Annual Exhibition of the Soros Center for Contemporary Art Chisinau. - Soros Center for Contemporary Art, Chisinau; Adams, Brad; Bulat, Vladimir; Ciobanu, Constantin; Esanu, Octavian; Gould, Claudia; Susara, Pavel; West, Steve (Chisinau : Soros Center for Contemporary Art, 1996)
Braila, Pavel ; Bulibas, Ion ; Cibotari, Iurie ; Dragnev, Lilia ; Dorosenko, Victor ; Druta, Veaceslav ; Ermurache, Alexandru ; Macari, Lucia ; Puscas, Mircea ; Sadovnicov, Stefan ; Scerbina, Igor ; Schiopu, Alexandru ; Tarna, Valentin ; Tinei, Alexandru ; Verlan, Mark
biografie
6th Kilometer , 1st annual exhibition of the Soros Center for Contemporary ARt, Chisinau, November 14-25, 1996
Engels
boek